Isometric muscle training of the spine musculature in patients with spinal bony metastases under radiation therapy - Rief, Harald; Jensen, Alexandra D.; Bruckner, Thomas; Herfarth, Klaus; Debus, Jürgen (BMC cancer, 2011)
Osseous metastatic involvement of the spinal column affects many patients with a primary tumour disease of all entities. The consequences are pain both at rest and under exertion, impairments in going about day-to-day activities, diminished performance, the risk of pathological fractures, and neurological deficits. Palliative percutaneous radiotherapy is one of the therapeutical options available in this connection. The aim of this explorative study is to investigate the feasibility of muscle-training exercises and to evaluate the progression- and fracture-free survival time and the improvement of bone density, as well as to assess other clinical parameters such as pain, quality of life, and fatigue as secondary endpoints.